Targeted subsidy plan and Kakwani index in Iran health system - Jafar Yahyavi Dizaj; Zohreh Anbari; Ali Kazemi Karyani; Yousef Mohammadzade (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Health care is considered as a human right, and fair financial contribution to health care plays an important role in providing effective services for all members of society. This study aimed at investigating the effects of targeted subsidy plan (since 2010) on equality in health-care financing in Iran from 2004 to 2014. MATERIALS AND METHODS: This was a descriptive-analysis, cross-sectional study that was conducted using data obtained from households' expenditure-income survey that is performed every year by the Statistical Center of Iran. The Lorenz curve, Gini coefficient, and Theil index were applied to measure inequality in healthcare expenditures (HEs). Furthermore, the Kakwani index was used to examine inequality in health-care finance during the study period. The analysis was performed using Stata version 13. RESULTS: Kakwani index was negative for all the studied years, except 2007. The value of this index was equal to −0.032, −0.045, and −0.046 in 2004, 2008, and 2014 for rural areas and was equal to −0.041, −0.029, and −0.0001 for urban areas, respectively. Despite the Kakwani index has been negative for most of the years, which reflects regressive financing in health care, there is no significant change in the trend of this indicator after the implementation of the subsidies. In addition, this indicator is moving toward being positive (progressive) in urban areas in 2014, which represents increased share of the poor in health payments. CONCLUSIONS: According to the results, the targeted subsidy plan could not reach to its purpose in health-care system for supporting the poor from HEs. It is recommended for policy-makers to design a specific plan for health-care financing and to allocate some defined resources such as taxes or subsidies to health-care sector.